An Excellent Seminary President - Aleshire, Daniel O. (Interpretation, 2025)
Excellent leadership of a theological school requires the ethical use of power in service to a school?s mission. It involves a spirituality that brings helpful perspective for disappointments in the present and hope for the future. Excellent leadership entails intelligence, humility, discipline, and the skills of building an effective administrative team, working well with the faculty, raising and administering financial resources, and nurturing a vision that both undergirds present tasks and cultivates a path to the future. This work is most faithfully accomplished with a theological and biblical undergirding in the long tradition of the mission of God in the world.